Kadar Vitamin D dengan Sindrom Mata Kering pada Karyawan - Margo, Eveline; Meiyanti, Meiyanti; Kartadinata, Erlani; Kartadinata, Noviani (Jurnal Biomedika dan Kesehatan, 2023)
Background Dry eye syndrome (DES) is the most common eye disease with a prevalence of around 5 – 50% of the worldwide population. In Indonesia alone, the prevalence of DES is around 27.5%. DES is a multifactorial disorder indicating that inflammation plays an important role in the pathophysiology of DES. The inflammation causes increased oxidative stress which can cause decreased tear production and inflammation on the ocular surface can cause an increase in excessive tear evaporation, causing instability of the tear film. Vitamin D has an anti-inflammation effect. The role of vitamin D in the eye through receptor vitamin D (VDR), which is expressed in the retinal pigment epithelium, retinal photoreceptors, ganglion cells layer, ciliary body, lens, cornea epithelium, and endothelium, as well as in aqueous humor, vitreous humor, and tears film. Vitamin D deficiency is said to have a contribution to DES. For that reason, this study aims to examine the relationship between vitamin D levels with DES. Methods The research design in this study was an observational analytic with a cross-sectional approach, which was followed by FK USAKTI employees in February – March 2021. Fifty-seven employees aged 25 – 60 were according to criteria and willing to take part in this study. OSDI questionnaire, Schimer’s test and tear break-up time (TBUT) were used to examine DES. Examination of vitamin D by measuring 25(OH)D levels. The data were analyzed using a chi-square test with significance level p<0.05. Results The vitamin D levels examination with DES using Schimer’s test was found to be unrelated (p=0.948), comparing vitamin D levels with the TBUT test, it was found significantly related to DES (p=0.030), meanwhile using the OSDI questionnaire was found to be unrelated (p=0.285). Conclusions There is a significant relationship between vitamin D levels and DES through TBUT examination.